Genetic variability for total carotenoid concentration in selected tropical maize (Zea mays) inbred lines - SIVARANJANI, R; PRASANNA, B M; HOSSAIN, F; SANTHA, I M (The Indian Journal of Agricultural Sciences, 2026)
A panel of 111 Indian and exotic maize (Zea mays L.) inbred lines were analyzed for total kernel carotenoid concentration. The study revealed significant genetic variability for the target trait, with concentration ranging from 6.5 to 67.3 µg/g with a mean of 26.9 µg/g. Among the genotypes analyzed, HPLET-03-36 developed under Maize HarvestPlus program at CIMMYT-Mexico recorded the highest total carotenoid concentration of 67.3 µg/g, followed by HPLET-0337 (63.2 µg/g), HPLET-03-35 (59.9 µg/g), BLSB-RIL17 (57.0 µg/g), BLSB-RIL43 (56.7 µg/g), HPLET-03-41 (56.1 µg/ g) and BLSB-RIL95 (50.9 µg/g). While the mean total carotenoid concentration in the HarvestPlus lines was 34.1 µg/g, the mean value for the target trait in the Indian maize lines was 23.8 µg/g. Selected inbreds from RIL populations developed using CM140 and CA00106 showed transgressive segregation for total carotenoid concentration. The average total carotenoid concentration among the deep orange inbred lines were 31.1 µg/g, while the same was found to be 28.03 µg/g, 23.97 µg/g, and 16.13 µg/g among the orange, yellow and pale yellow kernel classes of inbred lines, respectively. However, the range for total carotenoid concentration in each of the coloured classes (excluding white) varied considerably. Positive correlation was found between kernel colour and total carotenoid concentration; deep orange kernel colour genotypes, ingeneral, recorded higher levels of total carotenoid as compared to those with yellow or light yellow kernel colour. Identification of maize inbreds with high total kernel carotenoid concentration in the present study provides a strong opportunity for utilizing these promising genotypes in breeding for carotenoid-rich maize germplasm.